Kidney Stone Treatment Using the Percutaneous Nephrolithotomy Method (PCNL) - Novera, Rusliani S.; Angelica, Apriliana; Maharaja, Dwi P.; Situmorang, Stefani; Irawati, Wahyu (Jurusan Biologi FMIPA Universitas Cenderawasih, 2025)
Kidney stones are a serious condition that often occurs in the wider community. The presence of this disease is influenced by genetic factors, diet, dehydration, irregular lifestyle, and unhealthy lifestyle. One of the treatments used to treat kidney stones is Percutaneous Nephrolithotomy (PCNL) for kidney stones measuring more than two centimeters. This study aims to find out about kidney stone treatment using the PCNL method. The method used is a literature study by discussing five study focuses, namely (1) healthy kidney structure and its role in maintaining body balance, (2) kidney structural abnormalities and their impact on health, (3) kidney stone treatment methods and their impact on health, (4) PCNL as a modern treatment solution for kidney stone sufferers, and (5) the process of implementing PCNL in kidney stone treatment. It can be concluded that healthy kidneys are vital organs with integrated structures and functions to maintain the physiological balance of the body and play a role in producing the hormones renin, erythropoietin, and calcitriol. Kidney disorders that often appear are kidney stones caused by waste in the blood or crystallized chemicals such as calcium and oxalic acid. Pharmacological therapy is a therapy that is often used to treat kidney stones using medical drugs and also surgery, but this method has side effects due to the drugs given. PCNL is a non-invasive treatment that utilizes sophisticated medical technology to treat kidney stones. PCNL treatment is done by making a small incision in the skin of kidney stone sufferers so that it does not have significant side effects. PCNL has a high success rate for the treatment of kidney stones